Lessons from Covid 19 experience for African governments: towards environmental sustainability - Peter Bisong Bisong (Center for Humanities and Innovation Studies, 2020)
Covid 19 is an unfortunate situation that nevertheless could be said to have produced environmentally beneficial results. It has forced Africans and humanity in general to change attitudes and lifestyles that were hitherto inimical to the environment to ones that could restore the environment. For the sake of survival, consumerism, which is one of the greatest hallmarks of Africans and a source of depletion of earth resources, has given way to frugality; transportation activities that is one of the greatest sources of global warming have significantly reduced and most importantly human population which has terrifically posed as a threat to the survival of the environment is being forcefully checked. These and many other life changes in human beings, though accidental, are healing the environment, and the paper argues that if they are sustained, the environment will be restored to sound health. Most of these changes will naturally be sustained even after the Covid 19 pandemic, for as Aristotle acknowledged, actions perpetrated for a long time become habituated. However, the author believes that if conscious efforts are made to sustain these changed attitudes, then the environmental crisis currently enveloping the globe will be halted. The paper using philosophical methods of criticality and argumentation, concludes that Covid 19 though tragic for humans, nevertheless has lessons that could be useful for the present drive to sustain the environment and prevent future pandemic that could be environmentally related. The paper argues vehemently that African governments must steer their developmental agenda towards environmental sustenance in line with Covid 19 seeming directives to humanity.